2021
DOI: 10.1515/nanoph-2020-0660
|View full text |Cite
|
Sign up to set email alerts
|

The experimental evidence of a strong coupling regime in the hybrid Tamm plasmon-surface plasmon polariton mode

Abstract: Total internal reflection ellipsometry was employed for the excitation and study of hybrid Tamm plasmon-surface plasmon polaritons mode. Simple optical methodology using optical filters to cut the part of incident light spectra was proposed. Using optical filters measured energy spectra was divided into two parts where in each range only one branch of the hybrid TPP-SPP plasmonic mode was excited directly by the incident light. Present experimental studies have shown, that if the investigated system is in stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…In the model, the dispersions were described by two Lorentz oscillators which influence each other with equal strengths. 40 The splitting frequencies of two coupled harmonic oscillators can be written as:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the model, the dispersions were described by two Lorentz oscillators which influence each other with equal strengths. 40 The splitting frequencies of two coupled harmonic oscillators can be written as:…”
Section: Resultsmentioning
confidence: 99%
“…In the model, the dispersions were described by two Lorentz oscillators which influence each other with equal strengths. 40 The splitting frequencies of two coupled harmonic oscillators can be written as:where ω ± -corresponds to the resonance frequencies of TPP and SPP components of the hybrid mode, ω is the free Bragg mode frequency which is not involved in the strong coupling and g is the coupling strength. ω was treated as a function of the angle of incidence ω j = ω j ( θ ).…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that the surface lattice arrays influence the propagation length of the hybrid Tamm surface plasmon polaritons modes under strong coupling [ 21 ]. The decreasing losses were also achieved in hybrid Tamm plasmon polariton modes due to strong coupling between them [ 22 ]. By achieving the conditions needed for both plasmonic excitations, a new state of hybrid TPP-SPP mode appears [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…TPPs have an in-plane wave vector, which is less than the wave vector of light in a vacuum, which allows for their direct optical excitation, while for the SPPs to achieve a total internal reflection condition, the incident light has to reach an in-plane wave vector equal to the surface plasmon resonance [ 20 ]. Hybrid Tamm plasmon–surface plasmon polariton modes in a strong coupling regime [ 21 ] have been also applied for gas [ 22 ] and biosensing applications [ 15 ]. In this case, the Tamm plasmon component was used for enhanced performance of the SPP component in the TIR configuration.…”
Section: Introductionmentioning
confidence: 99%